Структура комплексу дощових черв’яків родини Lumbricidae сірих лісових ґрунтів Волинської височини - Бусленко, Леся; Щепна, Леся; Buslenco, Lesya; Schepna, Lesya. (Східноєвропейський національний університет імені Лесі Українки, 2015)
На перелогах формується комплекс люмбрицид, який у сірих лісових ґрунтах представлений 9-ма видами. На ранніх етапах їх природного заліснення збільшується чисельність підстилкових та ґрунтово-підстилкових видів.Earthworms (Lumbricidae) are аn important chain in organic matter transformation and in the maintaining ecological stability of soil biota in terms of Volyn Highland. Successional processes are accompanied by changes of structure and abundance lumbricids in biogeocenoses. Species of Aporrectodeа caliginosa, A. rosea, A. trapezoidеs are dominat in gray forest soils adapted to antropogenic disturbance. The complex of earthworms upland meadows is formed and represented by 9 species in soils of uncultivated fields. Earthworm species structure in fallow land of all ages until their afforestation remains constant. During afforestation earthworms complex Lumbricidae enriched forest species. Natural balance is restored. in anthropogenically-disturbed ecosystems.
The Structure in Complex of Earthworms Lumbricidae of Gray Forest Soils of Volyn Highland
Keywords: дощові черв’яки; люмбрициди; морфо-екологічні групи; сукцесія; перелоги; заліснення; earthworms; lumbricids; morpho-ecological groups; succession; fallow; afforestation